Ultrastructural features and differentiation of the spermatids in Brycon orbignyanus during the spermiogenesis - Aires, Eduardo Duarte; Stefanini, Maíra Aparecida; Orsi, Antonio Marcos (Brazilian Journal of Veterinary Research and Animal Science, 2000)
Spermiogenesis in Brycon orbignyanus may be divided in four stages, which consist mainly in reduction of cytoplasmic, nuclear and cellular volumes and compactation of the nuclear chromatin, whose stages of the process occur simultaneously. At the end of the spermiogenesis, when the spermatids reach high levels of differentiation, the nuclei become more compact and cytoplasms become reduced. These modifications result in the formation of new highly differentiated cells, the spermatozoa. Spermatozoa may be observed predominantly in cysts, like spermatids, or inside the lumen of the seminiferous tubules. Ultrastructurally, three different parts have been clearly identified in Brycon orbignyanus spermatozoon: head, middle-piece and flagellum.